Accurate Closed Form expressions for Conductor Loss and Dielectric Loss in Thin Film Microstrip Line. Issue 1 (23rd February 2023) - Bansal, Ritu; Mishra, Sanjay Kumar; Kumar, Yogesh
Abstract: In this paper, two improved closed form expressions are presented, namely, conductor loss and dielectric loss. The improved conductor loss closed form expression is perturbation‐based model approach suggested by Holloway & Kuester. This model takes into account the frequency‐dependent nature of conductivity of thin film conductor and effect of strip thickness. The model of dielectric loss takes into account frequency‐dependent loss tangent and effective relative permittivity of dielectric. A comparison of the present models with the experimental results is also presented for the frequency range from 100 to 1000 GHz. Deviations of the models suggested from experimental results are also tabulated. Average deviation and maximum deviation for conductor loss are 9.26 and 11.56, respectively. Also, average deviation and maximum deviation for dielectric loss are 4.89 and 6.67, respectively.